2021
DOI: 10.1093/ejo/cjab050
|View full text |Cite
|
Sign up to set email alerts
|

Patients with juvenile idiopathic arthritis are at increased risk for obstructive sleep apnoea: a population-based cohort study

Abstract: Background and objectives Juvenile idiopathic arthritis (JIA), an autoimmune disease, has been proposed to be comorbid with obstructive sleep apnoea (OSA). We aimed at testing the hypothesis that patients with JIA may presented with high risk of OSA in a cohort study. Subjects and methods This is a cohort study including patients with JIA from 1999 to 2013 identified from a longitudinal health registry. A matched non-JIA cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…In this cohort study, we employed a nationwide population-based registry to provide epidemiological evidence on the risks of new-onset ED in patients with HPV infection. The effect of measurable confounders was minimized by PS matching [ 71 , 72 , 73 , 74 , 75 ]. Sensitivity and negative control analyses were conducted to manage residual confounding and to ascertain the impact of HPV infection on ED development.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort study, we employed a nationwide population-based registry to provide epidemiological evidence on the risks of new-onset ED in patients with HPV infection. The effect of measurable confounders was minimized by PS matching [ 71 , 72 , 73 , 74 , 75 ]. Sensitivity and negative control analyses were conducted to manage residual confounding and to ascertain the impact of HPV infection on ED development.…”
Section: Discussionmentioning
confidence: 99%
“…Standard mean difference (SMD) was estimated to ensure that the selection of (A) periodontitis cases and matched non‐periodontitis controls in Study A, and (B) fibromyalgia cases and matched non‐fibromyalgia controls in Study B, were not biased. When the SMDs were equal to or less than 0.05, the characteristics of both groups were considered similar 21 . Hence, matching the propensity score may balance the heterogeneity of baseline characteristics and underlying comorbidities between each arm in the two studies.…”
Section: Methodsmentioning
confidence: 99%
“…When the SMDs were equal to or less than 0.05, the characteristics of both groups were considered similar. 21 Hence, matching the propensity score may balance the heterogeneity of baseline characteristics and underlying comorbidities between each arm in the two studies.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…As tonsils gradually regress with age, it was suggested that their absence is conventionally considered not affecting the health of patients receiving tonsillectomy, and the adverse effects of tonsillectomy could be masked by inductive growth of the lymphoid tissue in other regions of nasopharyngeal associated lymphoid tissues (NALTs) 3 . Therefore, tonsillectomy is commonly performed in patients with indications including recurrent throat infections, recurrent infections with modifying factors such as peritonsillar abscess and multiple antibiotic allergies or intolerance, as well as obstructive sleep apnoea (OSA) 4,5 …”
Section: Introductionmentioning
confidence: 99%